AI for Predictive Health Monitoring: Applications in ICU Patient Outcome Prediction - Dr. R Gayathri; Dr. N. KANCHANA; Dr. M. Karthi; Dr. M. Kannan; Mrs. V. BAKYALAKSHMI (The Bioscan, 2025)
Healthcare has achieved substantial advancement through Artificial Intelligence integration because it enables better patient outcome evaluation and forecasting along with constant monitoring. Predictive health monitoring significantly enhances operations in Intensive Care Units (ICUs) by using AI-based models to examine large quantities of patient information for critical event prediction purposes along with intervention optimization. The document examines ICU patient outcome prediction through AI applications together with vital information about machine learning (ML) and deep learning (DL) methods and data entry and ethical aspects along with potential future developments.